Anesthesia, the developing brain, and dexmedetomidine for neuroprotection - Tsivitis, Alexandra; Wang, Ashley; Murphy, Jasper; Khan, Ayesha; Jin, Zhaosheng; Moore, Robert; Tateosian, Vahe; Bergese, Sergio (Frontiers in Neurology, 2023)
Anesthesia-induced neurotoxicity is a set of unfavorable adverse effects on central or peripheral nervous systems associated with administration of anesthesia. Several animal model studies from the early 2000’s, from rodents to non-human primates, have shown that general anesthetics cause neuroapoptosis and impairment in neurodevelopment. It has been difficult to translate this evidence to clinical practice. However, some studies suggest lasting behavioral effects in humans due to early anesthesia exposure. Dexmedetomidine is a sedative and analgesic with agonist activities on the alpha-2 (ɑ2) adrenoceptors as well as imidazoline type 2 (I2) receptors, allowing it to affect intracellular signaling and modulate cellular processes. In addition to being easily delivered, distributed, and eliminated from the body, dexmedetomidine stands out for its ability to offer neuroprotection against apoptosis, ischemia, and inflammation while preserving neuroplasticity, as demonstrated through many animal studies. This property puts dexmedetomidine in the unique position as an anesthetic that may circumvent the neurotoxicity potentially associated with anesthesia.